2019
DOI: 10.3389/fmars.2019.00565
|View full text |Cite
|
Sign up to set email alerts
|

Biochemistry of Barnacle Adhesion: An Updated Review

Abstract: Barnacles are notorious marine fouling organisms, whose life cycle initiates with the planktonic larva, followed by the free-swimming cyprid that voluntarily explores, and searches for an appropriate site to settle and metamorphoses into a sessile adult. Within this life cycle, both the cyprid and the adult barnacle deposit multi-protein adhesives for temporary or permanent underwater adhesion. Here, we present a comprehensive review of the biochemistries behind these different adhesion events in the life cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 151 publications
(276 reference statements)
4
79
0
Order By: Relevance
“…The limpets were then carefully detached from the thin PVCA sheet by peeling ( figure 2 a )—this minimized both damage to the soft pedal sole and possible contamination from other mucus types. Since our collection method was similar to that used to sample barnacle cement (‘primary cement’ is secreted naturally for attachment, while ‘secondary cement’ is secreted only during re-attachment [ 23 ]), we have adapted their terminology to define our three types of pedal mucus. The thin mucus layer found on the PVCA sheet, similar to the ‘adhesive’ mucus from Smith, was defined as ‘interfacial primary adhesive mucus’ (IPAM; figure 2 b ), while the mucus layer remaining on the pedal sole was termed ‘bulk primary adhesive mucus’ (BPAM).…”
Section: Methodsmentioning
confidence: 99%
“…The limpets were then carefully detached from the thin PVCA sheet by peeling ( figure 2 a )—this minimized both damage to the soft pedal sole and possible contamination from other mucus types. Since our collection method was similar to that used to sample barnacle cement (‘primary cement’ is secreted naturally for attachment, while ‘secondary cement’ is secreted only during re-attachment [ 23 ]), we have adapted their terminology to define our three types of pedal mucus. The thin mucus layer found on the PVCA sheet, similar to the ‘adhesive’ mucus from Smith, was defined as ‘interfacial primary adhesive mucus’ (IPAM; figure 2 b ), while the mucus layer remaining on the pedal sole was termed ‘bulk primary adhesive mucus’ (BPAM).…”
Section: Methodsmentioning
confidence: 99%
“…The formers are hydrophilic and located at the periphery of the cement complex, providing surface coupling with exterior surfaces through non-covalent interactions, and also interaction with interior hydrophobic bulk proteins. This model has been updated in the last years [10][11][12], including the notion that surface coupling relies on catechol groups, through various adhesive and cohesive forces, and that catechol, quinone, and lysine-based cross-linking are also involved in protein nanofibers' curing and proper holdfast to the adhesion surface [10]. However, in barnacles, the catechol groups responsible for β-amyloid fibrils' cross-linking of bulk proteins do not have a peptidyl origin, differently from other marine organisms, e.g., mussels and sandcastle worms; non-peptidyl catechol precursors and lysine are incorporated among bulk cement protein (CP52k and CP100k) fibrils through enzymatic reactions that involve peroxidases and lysyl oxidase [10], providing structure and mechanical characteristics to the composite.…”
Section: Introductionmentioning
confidence: 99%
“…It has already been demonstrated that amyloid fibrils are closely related to the attachment of the biofilm of bacteria and barnacle onto different material surfaces, [13,35] and the inner mechanism of the strong affinity between amyloid fibrils and other materials is under study. [36,37] Very recently, our group systematically investigated the mechanism of the robust adhesion of amyloid aggregates onto versatile substrates taking the phase-transited lysozyme nanofilm (PTLF) as a model system. [38] The results of acoustic wave analysis on the peeling process of nanofilm from the underlying substrate suggested that the reliable adhesion of PTLF on a material surface was supported by enriched surface chemistry of the nanofilm that involved in multiplex binding with material surfaces (Figure 2a).…”
Section: Interplay Between Amyloid Aggregates and Inorganic Nanomatermentioning
confidence: 99%